Synthesis and surface plasmonic properties of ultra-thick silver nanowires. (11th May 2016) - Hua, Jiaojiao; Wu, Fan; Fan, Fengru; Wang, Wenhui; Xu, Zhongfeng; Li, Fuli
Abstract: Metallic nanowires (NWs) possess significant potential for applications in integrated photonic and electronic devices at the nanoscale. Considering the manipulation of NWs and energy loss associated with surface plasmon polaritons (SPPs) modes which serve as signal carriers in the nanophotonic devices, NWs with large diameters are significant. In this work, we report a successive multi-step polyol process approach for the synthesis of ultra-thick silver nanowires (Ag NWs) and investigate their energy loss. Thin Ag NWs prepared in the first step are used as seeds for the further growth of thick Ag NWs in the subsequent steps, where Ag NWs with diameter as large as 1820 nm have been prepared. We further investigate the SPP propagation properties of these thick Ag NWs, and find that energy loss is decreased in Ag NWs with improved diameter. Our experimental results are important for the design and fabrication of SPP-based nanophotonic components and circuits.